Measurement of Choroidal Thickness Following Caffeine Intake in Healthy Subjects. (3rd May 2016) - Altinkaynak, Hasan; Ceylan, Erdinç; Kartal, Baki; Keleş, Sadullah; Ekinci, Metin; Olcaysu, Osman Okan
Abstract: Purpose : The aim of this study is to investigate the effect of 200 mg caffeine on subfoveal choroidal thickness (CT) in the macular area as measured by enhanced depth imaging optical coherence tomography (EDI-OCT) in healthy subjects. Materials and methods : Fifty healthy individuals (study group) and 50 healthy individuals (control group) were enrolled in study. In the study group, participants received a 200 mg caffeine capsule and the control group consisted of subjects who received plasebo capsule. The subfoveal CT was measured by EDI-OCT before the caffeine intake and at 30 min, 1 h, 2 h, 3 h, 4 h and 6 h following caffeine intake. Results : SFCT after caffeine intake was significantly decreased at 30 min, 1 h, 2 h, 3 h and 4 h compared to the baseline measurement, while the difference between baseline and 6 h was not statistically significant in the study group. There were no significant differences between the baseline and the other measurement times in the control group ( p  > 0.05). Conclusion : The thinning of CT begins about 30 min after the oral ingestion of 200 mg of caffeine and lasts for about four hours.